Produção de inóculo, efeito de extratos vegetais e de fungicidas e reação de genótipos de soja à Sclerotinia sclerotiorum - Garcia, Riccely Ávila (2008)
Stem white rot, caused by S. sclerotiorum, has increased in fields cultivated with soybean due to the cropping of highly susceptible species during winter and the use of seeds contaminated with S. sclerotiorum. Studies involving inoculum production, alternative and chemical control, inoculation methodology and soybean genotypes resistance to Sclerotinia sclerotiorum consisted on the objectives of this work. The experiments were done in the Laboratório de Micologia e Proteção de Plantas LAMIP at the Universidade Federal de Uberlândia. The isolates used were obtained form soybean plants from Jataí-GO and Indianópolis-MG. Culture media amended with cornmeal were the most promising for sclerotium production both for yield and for the number of sclerotia. Culture media containing common beans and sunflower were the best ones. The number of sclerotia and yield decreased as the doses of cornmeal, bulgur wheat and cassava crumbs increased. The concentration of 20% yielded the greatest production of sclerotia for all three amendments. In relation to the alternative control, the results indicate that the greatest inhibition of mycelial growth was directly related to the increase of Azadirachta indica doses. The interaction A. indica with Pongamia glabra was significant, and the dose of 1/3 P. glabra was the most effective, with 65% inhibition. Of all vegetable extracts, the fruit of Piper aduncum was the most effective for reducing mycelial growth, with 43% inhibition. The results of "in vitro" chemical control demonstrated that the fungicides flutriafol, fluazinam, propiconazole, epoxiconazole + piraclostrobin, tebuconazole + trifloxistrobin, tebuconazole, ciproconazole + propiconazole, cyproconazole, fluquinconazole, tetraconazole, procymidone, iprodione, ciproconazole + trifloxistrobin, epoxiconazole, myclobutanil and difenoconazole inhibited more than 98% of the mycelial growth for both isolates. In the in vivo trial differences were noted for the fungicide effect, applied either preventively or as a curative. The fungicide iprodione best controlled the disease for both types of application. The results of inoculation of different soybean growth stages demonstrated that the smallest percentages of disease severity were directly proportional to plant age, and the best stage for inoculating the plants were V2 (leaves and stems) e V3 (leaves). The most consistent inoculation method was the permanent disk, for detached organs and for the whole plant, resulting in a significant correlation. Only 19 soybean genotypes performed as resistant or moderately resistant by the detached leaf method. When whole plants were inoculated, only two of these were moderately resistant, while all others were moderately susceptible or susceptible, generating a non significant correlation. CHAPTER 2: Sclerotia are fundamental for the life cycle of Sclerotinia sclerotiorum because they are the resting structures that form apothecia and, consequently, ascospores, and the hyphae. Studies involving this pathogen require inoculum availability; thus, the objective of this study was to evaluate vegetable growth media and the concentrations of cornmeal, cassava crumbs and bulgur wheat for sclerotium production. The vegetable culture media analyzed were: carrot, cabbage, soybean, cauliflower, common beans, sunflower, snap beans, potato, sweet potato and pumpkin, with or without the amendment of cornmeal. The concentrations of cornmeal, wheat and cassava crumbs amended on the common beans medium were 0, 5, 20, 35, 50, 65, 85 and 100%. The culture media of both tests were moistened with distilled water. The Erlenmeyers flasks containing the media were sterilized at 120ºC, for 20 minutes. Twelve hours after the media had cooled to room temperature, 5 6-mm diameter mycelial plugs were inoculated into each flask. The flasks were incubated at 22 ± 3ºC and 12 hours lighting, for 30 days (vegetable based media) or 45 days (concentrations of cornmeal, wheat and cassava crumbs). The sclerotia were separated from the original media after the incubation period by washing in tap water on a 2 mm screen. The sclerotia were dried on paper towel for 48 hours at room temperature. Subsequently, the weight and number of sclerotia were determined. Culture media yield was determined based on the sclerotia weight. The culture media amended with cornmeal were more effective, regardless of the vegetable used as a base, for both yield and number of sclerotia, and within this group, the media based on common beans and sunflower were the best ones. Sclerotia yield and number decreased as the concentrations of cornmeal, wheat and cassava crumbs increased. The concentration of 20% yielded the greatest production of sclerotia, and cornmeal and wheat were more effective at that. CHAPTER 3: The constant use of pesticides in agriculture has brought an interest for the search of natural products and production systems that cause less impact on man and the environment. Plants present a great diversity of substances in their composition and, oftentimes, these can present fungicide or fungistatic potential, and are being studied for the synthesis of new fungicides as well as for the induction of plant resistance, or, still, to be used directly by the farmer in the form of plant extracts on the crops. Considering that S. sclerotiorum is one of the most important pathogens in soybeans and other crops, this study analyzed the effect of vegetable oils and water extracts on the fungus mycelial growth. Concentrations of 25, 50, 75 and 100 ppm of the active ingredient azadiractine of Azadirachta indica oil were studied in association with the doses of 0, 1/3, 1/6, 1/8 and 1/10 of Pongamia glabra oil. The doses of P. glabra were obtained in relation to the volume of A. indica oil used to obtain the concentrations 25, 50, 75 and 100 ppm of A. indica. The trial with vegetable water extracts used the following plants: Peruvian pepper tree (Schinus molle L.), goatweed (Ageratum conyzoides L.), holy basil (Ocimum spp. L.), absinth wormwood (Artemisia absinthium L.), jamun (Syzygium cumini (L.) Skeels), common rue (Ruta graveolens L.), cassava (Manihot esculenta Crantz), white cedar (Melia azedarach L.) e matico (Piper aduncum L.). The vegetable extracts were incorporated to PDA at the concentration of 30%. The plant parts analyzed were the leaves, with the exception of the pepper, which, besides the leaves, the fruit was also tested. The control treatments were non amended PDA as a negative control and the fungicide procimidone at 10 ppm active ingredient as a positive control. The experimental design was completely randomized, with three repetitions (test of vegetable oils) and 5 repetitions (test of vegetable water extracts). The treatments were added after autoclaving the medium PDA, at low temperature. Subsequent to media solidification 6-mm diameter mycelial disks were inoculated on the center of the Petri plates and incubated at 22 ± 3ºC and 12 hours lighting for 48 hours. Evaluations started 24 hours after inoculation and lasted for 48 hours, when the negative control treatment had taken the whole plate surface. Mycelial growth inhibition percentage was calculated. The results indicated that greater mycelial growth inhibition was directly proportional to increasing concentration of A. indica and P. glabra. The interaction between A. indica and P. glabra was significant and the dose of 1/3 P. glabra was the most effective, with 65% inhibition. No dosage inhibited 100% of the mycelial growth as the fungicide. The water extract of the fruit of Piper aduncum was the most promising for the reduction of mycelial growth, with 43% inhibition. CHAPTER 4: Chemical control of soybean stem white rot is done based on previous studies about white rot on common beans. This study evaluated fungicides of different chemical groups on S. sclerotiorum in vitro , selecting them for in vivo trials. The fungicides flutriafol, fluazinam, propiconazole, epoxiconazole + piraclostrobin, tebuconazole + trifloxistrobin, tebuconazole, cyproconazole + propiconazole, cyproconazole, fluquinconazole, tetraconazole, procymidone, iprodione, cyproconazole + trifloxistrobin, epoxiconazole, vinclozolin, prothioconazole, azoxistrobin + cyproconazole, chlorothalonil + thiophanate-methyl, flutriafol + thiophanate-methyl, myclobutanil, difenoconazole, carbendazim, benomyl, carboxin + thiram, methyl thiophanate, quintozene, pencycuron, chlorothalonil and azoxistrobin were evaluated for controlling mycelial growth of two S. sclerotiorum isolates, from Jataí-GO and Indianópolis-MG, in a completely randomized design, with three repetitions. After the media containing 100 ppm active ingridient solidified, 6-mm diameter mycelial plugs were inoculated in the center of the Petri plates. The plates were incubated at 22 ± 3ºC and 12 hours lighting. Growth evaluations started 24 hours after inoculation and lasted for 48 hours for the isolate from Jataí and 72 for the one from Indianópolis. Mycelial growth percent inhibition was calculated. The in vivo trial was done only with the isolate from Jataí with inoculation on cultivar FMT Tabarana at the stage V3. The fungicides used in preventive and curative applications were fluazinam, epoxiconazole + piraclostrobin, tebuconazole + trifloxistrobin, tebuconazole, cyproconazole + propiconazole, procymidone, iprodione, vinclozolin, prothioconazole, azoxistrobin + cyproconazole and thiophanate methyl. The experimental design was completely randomized, with 4 repetitions. Evaluations were done 72 hours after inoculation at 22 ± 3ºC and 12 hours lighting, using a diagrammatic scale made with the program Quant. In vitro results demonstrated that the fungicides flutriafol, fluazinam, propiconazole, epoxiconazole + piraclostrobin, tebuconazole + trifloxistrobin, tebuconazole, cyproconazole + propiconazole, cyproconazole, fluquinconazole, tetraconazole, procymidone, iprodione, cyproconazole + trifloxistrobin, epoxiconazole, vinclozolin, prothioconazole, azoxistrobin + cyproconazole, chlorothalonil + thiophanate methyl, flutriafol + thiophanate methyl, myclobutanil and difenoconazole inhibited more than 98% of the mycelial growth of both isolates. There were significant differences on the fungicide effects in the in vivo trial, applied both preventively and curatively. The fungicide iprodione had the best performance on disease control for both modes of action. CHAPTER 5: The reaction of soybean genotypes to Sclerotinia sclerotiorum, as well as the phenological stages and inoculation methods for the selection of genotypes resistant to stem white rot has not been well determined. Therefore, this study determined the best phonological stage and inoculation method for S. sclerotiroum in soybean genotypes and studied partial resistance to stem white rot. The phenological stages analyzed for inoculation were Vc, V2, V3, V4 and R1 of cultivars MG/BR-46 (Conquista) and M-Soy 8200. The inoculation methods tested were a permanent PDA mycelial plug, which remained on the plant until evaluation, a plug for 24 hours, and a touch plug, which was placed on the leaf and immediately removed. Inoculations were done both on detached leaves and stems, as well as on intact plants of both cultivars. Soybean genotype resistance reaction was analyzed on 90 soybean genotypes inoculated with a permanent PDA plug on detached leaves placed on gerboxes. The genotypes that were resistant or moderately resistant were re-evaluated with inoculations on the whole plants. Evaluations were done 72 hours after incubation at 22 ± 3ºC and 12 hours lighting, based on a diagrammatic scale prepared with the program Quant. The experimental design was completely randomized, with 3 repetitions. The results indicated that the smallest disease severity was directly proportional to plant age, and the ideal stage for inoculation were V2 (leaves and stems) e V3 (leaves). The permanent mycelial plug was the best inoculation method for S. sclerotiorum for both soybean cultivars, and detached organs as well as the whole plant, in a significant correlation. Only 19 soybean genotypes performed as resistant to moderately resistant by the detached leaf inoculation test. However, when these genotypes were tested as intact plants, only 2 were moderately resistant, while all others were moderately susceptible to susceptible. In this case, the correlation was not significant, possibly due to the number of genotypes used (only two susceptible), for the evaluation of inoculation methods, and 19 with a different reaction for resistance evaluation.